The Social Behavior Ecosystem in Influencing Impulsive Buying Among University Students - Dhian Puspita (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: The phenomenon of impulsive buying often occurs in modern social life, especially as a response to social exclusion. Those who are excluded tend to adopt impulsive consumption behavior as a strategy to gain a sense of belonging and improve social relationships. In addition, the rapid development of online shopping platforms further strengthens this tendency. Therefore, it is important to understand the internal mechanisms that connect the two. Method: This study used SPSS 25.0 and WarpPLS 5.0 to analyze data from 385 respondents collected through questionnaires. Results: The focus of this study is to explore the internal mechanisms between social exclusion and impulsive buying behavior, with the following results: (1) Social exclusion has a positive correlation with impulsive buying behavior. (2) Relative deprivation acts as a mediator in the relationship between social exclusion and impulsive buying behavior. (3) The need to belong also functions as a mediator in the relationship. (4) Self-control acts as a moderator in the relationship between social exclusion and impulsive buying behavior. Novelty: The conclusion in this study aims to clarify the internal mechanism of impulsive buying behavior and provide recommendations for students to improve their self-control.